Diethyl Sulphate Induced Micromutations in Fenugreek - Mathur, V L; Sharma, G S (Annals of Arid Zone, 2016)
(Trigonella foemum graecum L.) seeds were treated with diethyl sulphate (dES) and Ml generation was raised. Twenty normal M1 plants were selected from each treatment to raise M2 generation. In M2 generation it was observed that the efficiency of dES and dES-R treatments at highest concentrations almost same in inducing genetic variability for yield contributing traits. dES treatments produced more number of superior progenies at different concentrations than dES-R treatments.